Feasibility and acceptability of an adapted environmental enrichment intervention for endometriosis: A pilot study - Nieves-Vázquez, Cristina I.; Detrés-Marquéz, Amanda C.; Torres-Reverón, Annelyn; Appleyard, Caroline B.; Llorens-De Jesús, Astrid P.; Resto, Ivana N.; López-Rodríguez, Verónica; Ramos-Echevarría, Paola M.; Castro, Eida M.; Flores, Idhaliz (Frontiers in Global Women's Health, 2023)
Introduction We have previously shown that Environmental Enrichment (EE)-consisting of social support, novelty, and open spaces—decreased disease progression and anxiety in a rat model of endometriosis. We developed a novel EE intervention to be tested in a pilot randomized clinical trial (RCT) in patients with endometriosis, a painful, stressful disease. Objective To translate and evaluate the feasibility and acceptability of an adapted EE intervention as an adjuvant to standard-of-care for endometriosis patients. Methods Feasibility was assessed through recruitment, enrollment, and adherence rates. Acceptability was evaluated through a post-intervention survey and focus group discussion 3-months after the end of the intervention. Results Of the 103 subjects recruited, 64 were randomized to the intervention group and 39 to the control group. At the start of the intervention, the study groups consisted of 29 (intervention) and 27 (control) subjects. Enrollment rates were 45.3% and 69.2%, and adherence rates were 41.4% and 100% for the intervention and control groups, respectively. Delays resulting from natural events (earthquakes, the COVID-19 pandemic) impacted enrollment and adherence rates. The most common reasons for missing an intervention were period pain (39.1%) and work-study (34.8%). There was high acceptability (>80%) of the intervention's logistics. The majority (82.4%) of subjects would continue participating in support groups regularly, and 95.7% would recommend the intervention to other patients. Conclusions We showed that EE could be translated into an acceptable integrative multi-modal therapy perceived as valuable among participants who completed the intervention. High attrition/low adherence indicates that additional refinements would be needed to improve feasibility. Acceptability data indicate that EE has the potential to be integrated into the clinical management of patients with endometriosis and other inflammatory, painful disorders. Studies are ongoing to assess the efficacy of EE in improving pain symptoms, mental health, and quality of life (QoL).